EFL Students' Metacognitive Awareness Listening Strategies in Higher Education - Yuli Shara Jepi Yanti; Indah Tri Purwanti; Maria Safriyanti (Universitas Islam Negeri Palopo, 2025)
This study aimed to examine the metacognitive awareness listening strategies that students commonly employ in their listening comprehension. The study used explanatory mixed-method research design. The data were acquired using a questionnaire adapted from Vandergrift (2006) and through an interview. The respondents in this study were fifth-semester students of the English Study Program at Riau University The respondents who filled out the questionnaire was 75 students of the 108 existing students. The results showed that students' metacognitive awareness in listening strategies were very high. The strategies were classified into: problem solving (4.00), mental translation (3.78), planning/evaluation (3.77), directed attention (3.58), and person knowledge (3.51). This result showed that most English Department students use problem solving as their listening strategy. It also shows that students often used their understanding of the context rather than translating word-for-word in their heads; compared the impact of their listening efforts; maintained concentration and stay focused in listening. In line with the qualitative data also showed that there were positive responses that students applied in using metacognitive listening strategies for their learning process. In the interview, students also shared some of the things they do when they lose focus. Such as pause the audio, relax the body and refresh the mind, and focus only on the key words. It also shows that students use more words they understand to guess the meaning of unfamiliar words. In addition, students make more comparisons between their background knowledge and their listening context.